Unsettled scores : politics, Hollywood, and the film music of Aaron Copland and Hanns Eisler - Bick, Sally (Music in American life., 2019)
The Hollywood careers of Aaron Copland and Hanns Eisler brought the composers and their high art sensibility into direct conflict with the premier producer of America's potent mass culture. Drawn by Hollywood's potential to reach--and edify--the public, Copland and Eisler expertly wove sophisticated musical ideas into Hollywood and, each in his own distinctive way, left an indelible mark on movie history. Sally Bick's dual study of Copland and Eisler pairs interpretations of their writings on film composing with a close examination of their first Hollywood projects: Eisler's score for 'Hangmen Also Die!' and Copland's music for 'Of Mice and Men.